MicroRNAs fingerprint of bicuspid aortic valve. (September 2019) - Sabatino, Jolanda; Wicik, Zofia; De Rosa, Salvatore; Eyileten, Ceren; Jakubik, Daniel; Spaccarotella, Carmen; Mongiardo, Annalisa; Postula, Marek; Indolfi, Ciro
Abstract: Aortic valve tissue is largely exposed to high blood flow. Cells belonging to aortic valve tissues are able to detect and respond to flow conditions changes. Bicuspid aortic valve (BAV) presents altered morphology, with only two abnormal cusps instead of three. This results in an alteration of blood flow dynamics on valve cusps and aortic wall, which may, in turn, increase the risk to develop aortic stenosis and/or regurgitation, endocarditis, aortopathy and/or aortic dissection. MicroRNAs (miRNAs) are short RNA strands regulating gene expression mainly through the inhibition of their target mRNAs. They are largely involved in cardiovascular pathophysiology and heart disease. More recently, it has been observed that the expression of specific miRNAs can be modulated in response to changes in hemodynamic conditions. Using a bioinformatic approach, this article analyses available scientific evidence about the differential expression of miRNAs in the bicuspid aortic valve, with a focus on the differential modulation compared to the calcific-degenerative tricuspid aortic valve. Highlights: Bicuspid aortic valve (BAV) results in an alteration of blood flow dynamics on valve cusps and the aortic wall. The expression of specific miRNAs can be modulated in response to changes in hemodynamic conditions. We identified miRNA involved in calcification, thrombosis and inflammation that might be exploited as future biomarkers of BAV.